Bioaugmentation With a Consortium of Bacterial Sodium Lauryl Ether Sulfate-Degraders for Remediation of Contaminated Soils - Rolando, Ludovica; Barra Caracciolo, Anna; Grenni, Paola; Mariani, Livia; Rauseo, Jasmin; Spataro, Francesca; Garbini, Gian Luigi; Visca, Andrea; Patrolecco, Luisa (Frontiers in Microbiology, 2021)
The anionic surfactant sodium lauryl ether sulphate (SLES) is the main component of most commercial foaming agents used in the excavation of highway and railway tunnels with Earth Pressure Balance-Tunnel Boring Machines (EPB-TBM). Several hundreds of millions of tons of spoil material, consisting of soil mixed with foaming agents, are produced worldwide, raising the issue of their handling and safe disposal. Reducing waste production and re-using by-products are primary objectives of the “circular economy” and in this context the biodegradation of SLES becomes a key question in reclaiming excavated soils, especially at construction sites where SLES degradation on the spot is not possible because of lack of space for temporary spoil material storage. The aim of the present work was to apply a bacterial consortium of sodium lauryl ether sulphate-degraders (BC) to spoil material excavated with an EPB-TBM and coming from a real construction site. For this purpose, the BC capability to accelerate SLES degradation was tested. Preliminary BC growth, degradation tests and ecotoxicological evaluations were performed on a selected foaming agent. Subsequently, a bioaugmentation experiment was conducted and the microbial abundance, viability and SLES concentrations in spoil material were evaluated over the experimental time (0.5, 3, 6, 24, 48 and 144 hours). Moreover, the corresponding aqueous elutriates were extracted from all the soil samples and analyzed for SLES concentration and ecotoxicological evaluations with the bacterium Aliivibrio fischeri. The preliminary experiments showed the BC capability to grow under 14 different concentrations of the foaming agent. The maximum BC growth rates and degradation efficiency (100 %) were achieved with initial SLES concentrations of 125, 250 and 500 mg/L. The subsequent bioaugmentation of the spoil material with BC significantly (six-fold) improved the degradation time of SLES (DT50 1 day) compared to natural attenuation (DT50 6 days). In line with this result neither SLES residues, either toxicity was recorded in the soil extracts, showing the spoil material as a by-product promptly usable. The bioaugmentation with BC can be a very useful for cleaning spoil material produced in underground construction where its temporary storage (for SLES natural biodegradation) is not possible.